Determinants of Postnatal Care Services among Mothers in Nakasongola Health Centre IV, Nakasongola District. - Asingo, Eunice Vivian; Frances Namukasa, Jane (Student's Journal of Health Research Africa, 2021)
Background: Poor utilization of postnatal services remains a serious maternal and child health challenge. Post Natal Services are defined as those services provided to both mothers and their infants immediately after birth up to 6 weeks of age. The postnatal period is a critical phase in the lives of mothers and newborn babies as most maternal and infant deaths occur during this time. In May, June, and July 2019, Nakasongola Health Centre IV, had 622 deliveries. However, there were only 229 postnatal attendances in the same period. A study was carried out to identify the determinants of postnatal care services utilization among mothers in Nakasongola Health Centre IV, Nakasongola District. Methodology: The study design was descriptive cross-sectional and it employed both quantitative and qualitative data collection methods. A sample size of 60 respondents was selected using the purposive sampling procedure. An interview guide was used to collect data. Results: 30 (50%) sometimes received support from their husbands to access postnatal care, 16 (26.7%) lack of awareness as a socio-economic factor, 14 (23.3%) poverty. 40 (67%) reported that cultural beliefs did not allow postnatal mothers to freely move and access health care services, 60 (100%) used herbs to treat the ailment in the postnatal period for various reasons. Half 30 (50%) resided 2 – 3 km away from Nakasongola Health Center IV and although 40 (67%) had ever used post-natal services at Nakasongola Health Center IV, 14 (35%) waited for 2 – 3 hours before receiving services yet all 60 (100%) agreed that long waiting time influenced service utilization. Conclusion and recommendations: Respondents faced various socio-economic, cultural, and health facility determinants of postnatal care services utilization among mothers. Sensitization about the availability of postnatal services and the importance of using these services, participation, and involvement of male partners among others.